2014
DOI: 10.1016/j.amc.2014.08.061
|View full text |Cite
|
Sign up to set email alerts
|

Global analysis of a schistosomiasis infection model with biological control

Abstract: a b s t r a c tIn this paper, the global stability of a schistosomiasis infection model that involves human and intermediate snail hosts as well as an additional mammalian host and a competitor snail species is studied by constructing Lyapunov functions and using properties of K monotone systems.We derive the basic reproduction number R 0 for the deterministic model, and establish that the global dynamics are completely determined by the values of R 0 . We show that the disease can be eradicated when R 0 6 1. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 13 publications
(28 reference statements)
0
14
0
Order By: Relevance
“…In reservoir host body, some cercariae survive and become adult shistosoma worm [3,6,7]. Several mathematical models are developed to study the spread of schistosomiasis in human, mammals, and snail population [8,9]. However, these two models do not take into account the density of the parasite in environment.…”
Section: Schistosomiasismentioning
confidence: 99%
“…In reservoir host body, some cercariae survive and become adult shistosoma worm [3,6,7]. Several mathematical models are developed to study the spread of schistosomiasis in human, mammals, and snail population [8,9]. However, these two models do not take into account the density of the parasite in environment.…”
Section: Schistosomiasismentioning
confidence: 99%
“…After the pioneering work of Macdonald [5], the dynamics properties (including stability, persistence, and oscillatory behavior) of the schistosomiasis models that have significant biological background have been one of the most active areas of research and have attracted great attention of many researchers. Many excellent and interesting results have been obtained (see [6]- [18]). Besides, a simplification of the two-strain, vector-host model was proposed by Feng and Velasco-Hernández [19] for Dengue fever.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, schistosomiasis cannot be eradicated if the only intervention is health education [13]. Diaby et al [15] proposed a schistosomiasis model with biological control, i.e., competitor-resistant snails. They found that competitor-resistant snails can be used to manage the spread of schistosomiasis.…”
Section: Introductionmentioning
confidence: 99%